Associations between bride price obligations and women's anger, symptoms of mental distress, poverty, spouse and family conflict and preoccupations with injustice in conflict-affected Timor-Leste. Issue 1 (26th May 2016) - Rees, Susan; Mohsin, Mohammed; Tay, Alvin Kuowei; Thorpe, Rosamund; Murray, Samantha; Savio, Elisa; Fonseca, Mira; Tol, Wietse; Silove, Derrick
Abstract : Objectives: Bride price is a widespread custom in many parts of the world, including in most countries in sub-Saharan Africa and parts of Asia. We hypothesised that problems relating to the obligatory ongoing remittances made by the husband and his family to the bride's family may be a source of mental disturbance (in the form of explosive anger and severe mental distress) among women. In addition, we postulated that problems arising with bride price would be associated with conflict with the spouse and family, poverty and women's preoccupations with injustice. Design: A mixed-methods study comprising a total community household survey and semistructured qualitative interviews. Setting: Two villages, one urban, the other rural, in Timor-Leste. Participants: 1193 married women participated in the household survey and a structured subsample of 77 women participated in qualitative interviews. Results: Problems with bride price showed a consistent dose–effect relationship with sudden episodes of explosive anger, excessive anger and severe psychological distress. Women with the most severe problems with bride price had twice the poverty scores as those with no problems with the custom. Women with the most severe problems with bride price also reported a threefold increase in conflict with their spouse and a fivefold increase in conflict with family. They also reported heightened preoccupations with injustice. Conclusions: Our study is the first to show consistent associations between problems with bride price obligations and mental distress, poverty, conflict with spouse and family and preoccupations with injustice among women in a low-income, postconflict country.